"I Should Probably Know More:" Reasons for and Roadblocks to the Use of Historic University Collections in Teaching. Issue 1 (26th June 2019) - Marcketti, Sara; Gordon, Jennifer F.
Collections of dress and textiles can make subjects such as history come to life. However previous studies have shown that many collections are underutilized within university settings. The purpose of this paper is to examine contributing and detracting factors for use. In-depth, semi-structured interviews were conducted with curators and collection managers (n = 15) at twelve institutions. Respondents were then asked to recommend faculty members who did (n = 9) or did not use the collection (n = 6). Through data analysis, four major themes were related by the collection managers including: 1) ambiguous roles and unknown collections, 2) continual need for collection management maintenance, 3) lack of process and access to the collections, and 4) misperceptions about the collections. Faculty that used the collection (n = 9) stated previous knowledge of the collection and the importance of material culture to student knowledge and understanding. Barriers as identified by those faculty that did not use the collection (n = 6) included lack of access and difficulty in scheduling time to use the collections.